Retenção discente no Centro de Ciências Humanas e Naturais da UFES : o caso dos cursos Letras-Português e Geografia - Moraes, Joana de Paula Boeno (2015)
With a growing number of college students currently, Brazilian higher education has faced up alarming rates on drop out and student retention, however, without overcoming this reality of study abandonment and unaccomplishment of demands for professional formation to meet labor market needs. Retention is here understood as a negative factor, referring to the student who is not able to graduate during the fixed time program, considering the specific academic calendar, thus, requiring a longer time to complete the course. Effort in research development and specific policies to contend the dropout and retention in Brazil are still unassertive and the Federal University of Espirito Santo (UFES) is one of the first institutions engaged in overcoming this problem through debates about the theme and through support for researches, such as Pereira´s (2013), which showed a panorama on classroom course retention at UFES. His research has shown, for example, that at the University Human and Natural Sciences Center (CCHN) there were graduation courses with a percentage over 80% of retained students, such as Geography and Letters-Portuguese major. This fact led to question: what are the main factors associated with student retention in morning and evening Portuguese in person courses and in morning and evening Geography in person courses at the Human and Natural Sciences Center? To identify possible indicators for retention, interviews and questionnaires were applied and semi-structured interviews were conducted with students classified as retention status on the graduation courses mentioned above, with the Human and Natural Sciences Center director and with the coordinators of the courses. Based on the content analysis method, and in light of existing theories and studies on national and international literature regarding unsuccessful completion of courses, the data analyses identified the retention indicators which were presented by categories: factors related to student individual characteristics, external and internal factors related to the institution. The university representatives also brought an institutional view of the issue. Therefore, institutional intervention actions were suggested for preventing and coping with unsuccessful completion of the courses